How do Muslim community members perceive Covid-19 risk reduction recommendations - a UK qualitative study? - Shaima M. Hassan; Adele Ring; Naheed Tahir; Mark Gabbay (BMC, 2021)
Abstract Introduction The evidence is now unequivocal that people from Black and Minority Ethnic Backgrounds (BAME) living in the UK are disproportionately affected by covid-19. There is growing evidence that the reasons for this difference are multi-factorial and need further exploration. Aim The aim of this study was to understand better, perceptions of risk and responses to covid-19 of members of the Muslim community living in the North West of England, and to understand the facilitators and barriers to adherence to restrictions and guidance measures. Method A total of 47 participants took part in 25 in-depth qualitative interviews and four focus groups (n=22) that explored perceptions of risk and responses to risk from covid-19. Data were analysed thematically. Findings Participants were aware of the mechanism of transmission of covid-19 and took steps to mitigate risk of transmission including, observing a range of hygiene practices and following social distancing guidance. Increased risk of covid-19 for BAME populations was explained largely in terms of exposure to the virus due to the types of employment people from BAME populations are employed in. Limitations both within the working environment and more generally in public spaces, was identified as problematic for effective social distancing. The closure of mosques sent out a strong message about the seriousness of the virus and religious teachings reinforced hygiene and social distancing guidelines. Conclusion Across society there are people that adhere to restrictions and guidelines and those that do not. Improving local information provision and communication pathways during times of the pandemic, could aid understanding of risk and promote adherence to social distancing restrictions.